International exposure : perspectives on modern European pornography, 1800-2000 - Sigel, Lisa Z., 1965- (Rutgers University Press, 2005)
International Exposure demonstrates the wealth of desires woven into the fabric of European history: desires about empire and nation, about self and other, about plenty and dearth. By documenting the diverse meanings of pornography, senior scholars from across disciplines show the ways that sexuality became central to the individual, to the nation, and to the transnational character of modern society. The ten essays in the volume engage a rich array of topics, including obscenity in the German states, censorship in France's Third Republic, "she-male" internet porn,